Highlighting Pakistan’s psychiatrist shortage amid a persistent mental health crisis - Ahmad, Ihtisham (Journal of the Pakistan Medical Association, 2025)
Madam, Mental health issues in Pakistan are becoming increasingly prevalent, yet the country continues to face a significant shortage of psychiatrists. Currently, the ratio of psychiatrists to the population stands at approximately one per 360,000 people, which is well below the World Health Organization’s standard of one per 100,000 individuals1. This shortage, along with insufficient resources for mental health services, significantly hinders access to essential psychiatric care for those in need. The growing mental health crisis is particularly evident in the recently deteriorating economic and political climate in Pakistan. Rising inflation, widespread unemployment, and an uncertain political landscape are leading to increasing rates of anxiety and depression among the population, often going undiagnosed and untreated. The National psychiatric morbidity survey of Pakistan in 2022 concluded that lifetime and current weighted prevalence of all psychiatric disorders is 37.91 % and 32.28 % respectively, and includes mood disorders, neurotic and stress-related disorders, psychotic disorders, and mental problems due to substance use2. As of 2022, The suicide mortality rate stands at 9.8 per 100,000 population and is increasing yearly3. Furthermore, the mental health workforce remains concentrated in urban centers, which is especially concerning since about 62% of the population lives in rural areas4. Moreover, the recent trend in Psychiatrists moving abroad for better opportunities exacerbates the already dire situation, resulting in an insufficient number of professionals to meet the increasing demand within the country. In response to this crisis, it is imperative to expand psychiatry training programmes and offer financial incentives and career development opportunities to help produce more psychiatrists and encourage them to remain in Pakistan. Telepsychiatry offers another promising solution, particularly in remote areas where professionals are less willing to serve in-person. Additionally, integrating mental health services into primary healthcare systems can ensure that every healthcare provider is equipped to diagnose and manage common psychiatric conditions. Public education campaigns aimed at reducing the stigma surrounding mental health are also essential to encourage individuals to seek the care they need. Addressing the shortage of psychiatrists in Pakatan is not only critical for the mental well-being of the population but also for the nation’s overall health outcomes, as it is evident that psychiatric conditions are associated with other chronic physical conditions5. It is vital that the government, healthcare providers and institutions collaborate to build a sustainable mental health system that can meet the needs of today and the future.